TEST PERFORMANCE OF SOLAR-BASED ICE-MAKING SYSTEM FOR SMALL-SCALE FISHERMEN IN TANIMBAR ISLANDS REGENCY, MALUKU, INDONESIA - Ayi Rahmat; Amanda Putri Auliansyah (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2026)
This study aims to evaluate the performance of solar-powered ice maker for small-scale fishermen in Tanimbar Islan Regency, Maluku, Indonesia. The Ice-maker system was built in December 2025. The research itself was conducted from 1 January to 10 January, 2026, and electrical data were collected by downloading online records of production and consumption of energy from photovoltaic system, conducting direct field observations, and carrying out of interviews with small-scale fishermen, ad were analyzed using descriptive-analytical approach. The results indicate that the utilization of solar energy for ice maker system to support small-scale fisherman is reliable. The system performance demonstrate that the installed photovoltaic system has capability to operate contiunously for 24 hours supplying energy for ice production. Although energy production flutuates due to weather variation condition, these changes do not disrupt the overall system operation. From the production perspective, all ice produced by the system was fully absorbed by small-scale fisherman, yet it has not fully met their total ice demand. Key words: fish, fishermen, ice-maker, photovoltaic, solar